COMUNICAREA PROFESIONALĂ: COMPORTAMENT INDIVIDUAL ŞI ACŢIUNE CORPORATISTĂ - COŞERIU, director adjunct, BM „B.P. Hasdeu”, Tatiana (BIBLIOPOLIS, 2020)
The article is about the results of the professional communication in the BM structures. The experiment was conducted on the behavior, management styles and groups cohesion. The experiment was an innovation in the institutional management